Relationships between perceived coach leadership and athletes` affective states experienced during competition - González-García, H.; Martinent, G.; Nicolas, M. (Journal of Sports Sciences, 2021)
We examined whether coach leadership behaviours predicted the intensity and direction of positive and negative affects experiencing during competition controlling for affects experienced within two hours before competition. A total of 296 athletes (33% female and 67% male; Mage = 21.61; SD = 6.32) voluntarily participated in the study. A partial least square path modelling (PLS-PM) approach was used to examine the relationships between the study variables. The results showed that coach social support significantly positively predicted the direction of negative affects during competition controlling for pre-competitive negative affect direction. Besides, results revealed that coach democratic behaviour marginally and negatively predicted Negative Affects direction during competition whereas coach autocratic behaviour marginally and negatively predicted Positive Affects intensity. Thus, coach social support emerged as an adaptive coaching behaviour. The usefulness of a longitudinal approach might reveal the multivariate experience of affects states and the manner to handle them from a coach leadership perspective.